TANGGUNG JAWAB HUKUM NOTARIS TERHADAP AKTA JUAL BELI HAK MILIK ATAS TANAH YANG DIBUATNYA DITINJAU DARI UNDANG-UNDANG NOMOR 30 TAHUN 2004 TENTANG JABATAN NOTARIS - Erwan Kemara, I Made; Dharma Kusuma, A. A. Gede Agung; Westra, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 09, September 2013)
Article titled Responsibility Notary / PPAT In Creating Deed Sale Freehold Land is written using normative research methods. The purpose of this paper is to determine the responsibility of Notary / PPAT if the deed of sale of land titles which made turned out to cause a dispute. Of searches conducted, it was found that the responsibility Notary / PPAT the deed of sale is made is limited to the early part of the deed / deed of head and tail deed or closing certificates, the certificate content section, a position Notary / PPAT can be equated as a witness against a legal act. Notary / PPAT not responsible for any inaccuracy materially advanced by the parties.
Keywords: Responsibility, Notary / PPAT, Sale and Purchase Agreements